PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP AKUNTABILITAS PENDAPATAN PAJAK DAERAH DI BADAN PENGELOLA PAJAK DAN RETRIBUSI KOTA MEDAN - Mas’ut Mas’ut; Abdan Masrura (Universitas Islam Islam Sumatera Utara, 2018)
This reaserch aims to examine the application effect of accounting information system to accountability of local tax revenue in the regional tax and retribution management board of Medan City. A number of the sample or respondent is 30 employees of the Regional Tax and Retribution Management Board of Medan. The data is gained through questioneires which are spread up among the respondents then processed by using SPSS program. Simple regression analysis is used to analyze and the result shows that the application of accounting information system (X) has given positive influence into the accountability of local tax revenue (Y). The coefficient of determination or R square figure amount to 75.4% and the remaining 24.6% is influenced by other variables which are not examined. Therefore, the Regional Tax and Retribution Management Board is supposed to maintain the application of accounting information system to increase the accountability of local tax revenue.